Longitudinal tract-based spatial statistics analysis of white matter diffusivity changes and cognitive decline during the transition from MCI to Alzheimer’s disease - Sewon Lim; Hajin Kim; Youngjin Lee (PLoS ONE, 2025)
Longitudinal studies that analyze the changes in the axial diffusivity (AxD) and radial diffusivity (RD) values over time can elucidate the progression of white matter damage and its causal relationship with cognitive decline. This study aimed to investigate the longitudinal changes in white matter integrity based on AxD and RD and their association with cognitive decline in patients with mild cognitive impairment (MCI) that progressed to Alzheimer’s disease (AD). Eighteen participants diagnosed with MCI at baseline and AD at the follow-up examination were selected from the AD Neuroimaging Initiative and included in this 2-year study Tract-based spatial statistics (TBSS) was used to assess longitudinal changes in WM. Voxel-wise and region-of-interest (ROI) analyses were conducted, and statistical models controlled for age, sex, education, and APOE ε4 status. Correlation and multiple regression analyses were performed to examine the association between AxD/RD changes and changes in clinical dementia rating (CDR) scores. Significant increases in AxD and RD were observed over 2 years in widespread WM tracts, including the corpus callosum, internal capsule, corona radiata, cingulum, superior longitudinal fasciculus, and fornix. AxD changes, particularly in the left retrolenticular internal capsule, left posterior corona radiata, left fornix, and right superior longitudinal fasciculus, showed significant correlations with cognitive decline. In contrast, RD changes were not significantly associated with CDR changes in any region. Multivariate regression analysis identified AxD in the left retrolenticular internal capsule as a significant independent predictor of CDR changes. AxD was sensitive to microstructural alterations in WM associated with cognitive decline during the transition from MCI to AD and may serve as a valuable biomarker for early detection and monitoring of AD progression. Longitudinal DTI analyses provide critical insights into the temporal dynamics of WM degeneration and its role in clinical deterioration.